Widespread pain is a risk factor for cardiovascular mortality: results from the Framingham Heart Study - Tesarz, Jonas; Eich, Wolfgang; Baumeister, David; Kohlmann, Thomas; D'Agostino, Ralph; Schuster, Alexander K. (European heart journal, 2019)
Aims: With the introduction of widespread pain (WSP) as a separate diagnostic code in the ICD-11, WSP has now become an own clinical diagnosis independent of the underlying pathophysiology. Research has reported aetiological associations of WSP and cardiovascular diseases. However, studies on mortality risk in individuals with WSP have reported inconsistent results. This study investigates whether there is increased mortality in WSP individuals and establish potential determinants of mortality risk. Therefore, we evaluates the population-based prospective cohort of the Framingham Heart Study (FHS). Methods and results: The FHS is a longitudinal multi-generational study. Pain status was assessed uniquely between 1990 and 1994. Cox proportional hazards modelling was used to estimate hazard ratios (HRs) of WSP on all-cause mortality controlling for sex and age, cardiovascular risk factors, cancer history, lifestyle factors and current medication. WSP examination was carried out in 4746 participants of the FHS (60.3 ± 13.5 years, 55.1% women). A total of 678 (14.5%) subjects fulfilled the criteria for WSP, whereas 4011 (85.5%) subjects did not. The follow-up time was 15 years, during which 202 persons died in the WSP group and 1144 in the no-WSP group. When adjusting for age and sex, all-cause mortality was increased by about 16% in WSP subjects. Individuals with WSP had an increased HR particularly for cardiovascular cause of death (HR adjusted by age and sex = 1.46, 95% confidence interval 1.10–1.94). Conclusion: Our data show that in a large population-based cohort, WSP is associated with increased HR for cardiovascular cause of death, underlining the need for pain assessments in cardiovascular practice.